2008
DOI: 10.1371/journal.pone.0003341
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific RNA Silencing of Mutant Ataxin-3 Mediates Neuroprotection in a Rat Model of Machado-Joseph Disease

Abstract: Recent studies have demonstrated that RNAi is a promising approach for treating autosomal dominant disorders. However, discrimination between wild-type and mutant transcripts is essential, to preserve wild-type expression and function. A single nucleotide polymorphism (SNP) is present in more than 70% of patients with Machado-Joseph disease (MJD). We investigated whether this SNP could be used to inactivate mutant ataxin-3 selectively. Lentiviral-mediated silencing of mutant human ataxin-3 was demonstrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 37 publications
4
127
0
1
Order By: Relevance
“…More recently, our group showed both in vitro and in a rat model of MJD that lentiviral-mediated silencing of the mutant human ataxin-3 was efficient and selective, allowing preservation of wild-type ataxin-3 (Alves et al, 2008a). Specific silencing has also been later reported to SNPs targeting ataxin-7 in SCA7 (Scholefield et al, 2009) and huntingtin in Huntington's disease (Zhang et al, 2009;Hu et al, 2009).…”
Section: Rna Interference-based Therapeuticsmentioning
confidence: 96%
See 1 more Smart Citation
“…More recently, our group showed both in vitro and in a rat model of MJD that lentiviral-mediated silencing of the mutant human ataxin-3 was efficient and selective, allowing preservation of wild-type ataxin-3 (Alves et al, 2008a). Specific silencing has also been later reported to SNPs targeting ataxin-7 in SCA7 (Scholefield et al, 2009) and huntingtin in Huntington's disease (Zhang et al, 2009;Hu et al, 2009).…”
Section: Rna Interference-based Therapeuticsmentioning
confidence: 96%
“…RNA interference (RNAi) is a powerful tool for selective knockdown of gene expression. Gene silencing by RNAi has been successfully used to downregulate the expression of mutant genes and rescue phenotype in various neurodegenerative diseases, including Huntington's disease Rodriguez-Lebron et al, 2005;DiFiglia et al, 2007, van Bilsen et al, 2008Lombardi et al, 2009;Pfister et al, 2009), familial forms of amyotrophic lateral sclerosis (ALS) (Raoul et al, 2005;Ralph et al, 2005;Azzouz, 2006), SCA1 (Xia et al, 2004), and MJD (Miller et al, 2003;Alves et al, 2008aAlves et al, , 2010Hu et al, 2009). …”
Section: Rna Interference-based Therapeuticsmentioning
confidence: 99%
“…The therapeutic utility of RNAi for SCA3 was first tested in the rat by targeting a SNP in the mutant allele. Reducing levels of the mutant allele rescued diseased phenotypes [104]. Later, work from the same group showed that shRNAs designed to be nonallele-specific, silenced both wild type and mutant ataxin-3, and rescued SCA3 phenotypes.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%
“…This specificity was achieved through lentiviral vectors encoding siRNAs that selectively target a SNP that occurs in over 70% of SCA3 patients. This allele specific mechanism decreased the severity of neurological pathogenesis associated with SCA3 [215]. Furthermore, independent studies used a similar mechanism, adeno-associated viral (AAV) vector based delivery of shRNA and small interfering RNA (siRNA) to rescue phenotypes in SCA1 [216] and SCA7 in affected mouse models, respectively.…”
Section: Suppression/modification Of Mutant Gene Expression and Protementioning
confidence: 99%